St. Mark's and the Social Gospel Methodist Women and Civil Rights in New Orleans, 1895-1965. - Blue, Ellen (Knoxville : University of Tennessee Press, 2011)
The impact of St. Mark & rsquo;s Community Center and United Methodist Church on the city of New Orleans is immense. Their stories are dramatic reflections of the times. But these stories are more than mere reflections because St. Mark & rsquo;s changed the picture, leading the way into different understandings of what urban diversity could and should mean. This book looks at the contributions of St. Mark & rsquo;s, in particular the important role played by women (especially deaconesses) as the church confronted social issues through the rise of the social gospel movement and into the modern.
Part IV: Post-1965 and ConclusionChapter 8: Since 1965; Chapter 9: Conclusion; Appendix A: Sources for Research on MECS Women's Work; Appendix B: A Charter of Racial Policies; Notes; Index.
Description based on print version record.
Keywords: Digital mapping; Geographic information systems; Geology -- Data processing; Soils -- Analysis -- Data processing; Religion; St. Mark's United Methodist Church (New Orleans, La.) -- History; St. Mark's Community Center -- History; Women in church work -- Louisiana -- New Orleans -- History; Civil rights -- Religious aspects -- Methodist Church -- History; Social gospel -- Louisiana -- New Orleans -- History; New Orleans (La.) -- Church history; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books